PENGARUH TINGKAT PENGANGGURAN TERBUKA DAN RATA-RATA LAMA SEKOLAH TERHADAP TINGKAT PENDUDUK MISKIN DI INDONESIA 2020 - Deswita Sari, Putri; Najla, Saniya; Desmawan, Deris (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This research was conducted because the poverty rate in 2020 increased to 0.67%. Therefore this study aims to analyze the partial and simultaneous effects of Open Unemployment and Average Length of School on the Poor Population Rate in Indonesia in 2020. This type of research is quantitative research. The analytical method used in this study is the normality test and hypothesis testing, and the data used is secondary data. The results of the study show that partially (1) there is no significant effect of open unemployment on the poverty rate in Indonesia in 2020, while simultaneously (2) there is no effect on the average length of schooling on poverty in Indonesia in 2020, (3) there is no significant effect Open Unemployment and Average Length of School to poverty in Indonesia in 2020.